Women in mechanical circulatory support: She persisted! - Benck, Kelley N.; Khan, Fatima A.; Munagala, Mrudula R. (Frontiers in Cardiovascular Medicine, 2022)
Many women physicians have blazed trails and played instrumental roles in advancing the field of Advanced Heart Failure (AHF), Mechanical Circulatory Support (MCS), and cardiac transplantation to its current recognition and glory. In contrast to other areas of cardiology, women have played an integral role in the evolution and emergence of this sub-specialty. Although the ceiling had been broken much later for women cardiothoracic (CT) surgeons in the field of AHF, the ingress of women into surgical fields particularly CT surgery was stonewalled due to pervasive stereotyping. The constancy, commitment, and contributions of women to the field of AHF and MCS cannot be minimized in bringing this field to the forefront of innovation both from technological aspect as well as in redesigning of healthcare delivery models. Integrated team-based approach is a necessity for the optimal care of MCS patients and forced institutions to develop this approach when patients with durable left ventricular assist devices (LVAD) began discharging from the hospitals to local communities. Women in various roles in this field played a pivotal role in developing and designing patient centered care and coordination of care in a multidisciplinary manner. While embracing the challenges and turning them to opportunities, establishing partnerships and finding solutions with expectations to egalitarianism, women in this field continue to push boundaries and subscribe to the continued evolution of the field of AHF and advanced cardiac therapies.